Effect of different extraction processes on the recovery of ghee residue proteins - MUNIRATHNAMMA, V; GUPTA, VIJAY KUMAR; MEENA, GANGA SAHAY (The Indian Journal of Animal Sciences, 2017)
Ghee residue (GR) is the by-product of ghee industry, possessing huge nutritional potential that still lacks in its valorization. This investigation was aimed to recover proteins from GR, by processing with different treatments such as boiling water (30 min), washing with 50% alcohol, isoelectric precipitation, boiling in sodium tri polyphosphate concentration (STPP) solution (1, 2, 3% strength, 30 min) and employing ultrafiltration membrane process. Extraction of proteins from the processed ghee residue (PGR) was observed to be of lower proteins purity. Commonly used acid precipitation method also failed to precipitate proteins from GR, but ultrafiltration resulted in efficient concentration of these proteins. Decrease in concentration of ghee residue and increase in dissolving time,significantly increased solubility of GR. Similarly, addition of sodium tri polyphosphate concentration (STPP) and dissolving time also significantly improved GR solubility. Ghee residue solution was concentrated up to 5.2 ultrafiltration (UF) folds, after that membrane flux approached to zero. Further, ultrafiltration of GR solution resulted in 97% recovery and 70% purity of GR proteins. Findings of this study could significantly increase the profit of organized dairy plants and significantly reduce the waste disposal problem. About 1,00,000 tonnes of proteins can be recovered annually from GR only; that can satisfy yearly protein requirement of about 45,66,000 healthy persons and might help the nation in combating severe problem of protein energy malnutrition.